Percepción de los problemas ambientales por parte de la población, en la ciudad de Indiana, distrito de Indiana, región Loreto. 2019 - Cardenas Bardalez, Girno Alberto (2021)
The objective of the research was to identify environmental problems and to know the degree of interest that the population has on the environmental problems that the population of the city of Indiana has. Random probabilistic sampling was used, where the sample of 269 people who reside in this city was selected. The results obtained from the surveys were interpreted through descriptive statistics. The variables evaluated were: perception and environmental problems, environmental attitude, commitment or social responsibility and environmental training, of the inhabitants of the city of Indiana. Regarding environmental knowledge and problems, they say that the word environment is related to natural resources (46.15%), environmental issues are currently very relevant (76.9%) and state that they always protect their environment (61.54%). Regarding environmental attitude, the main environmental problem of the city is the management of solid waste (61.54%) and they consider the seasonal flooding of the river as another environmental problem (15.38%) as well as the contamination of the surface waters of the Amazon river (15.38% ). They consider preserving the current environment for future generations (92.31%); they do not comply with environmental legislation due to the little knowledge they have of it (64.93%). They are responsible for the current situation of the city (53.85%) and in terms of municipal work they consider it to be regular (53.84%) to terrible (23.08%). 46.15% say that they did receive training on environmental issues. The environmental training, they receive is mostly through meetings (69.23%) and they affirm that the training greatly increases environmental awareness; recommend that to solve environmental problems in the city, environmental education programs should be developed (53.85%).